Progress in Preclinical Research on Mesenchymal Stem Cell-Derived Exosomes for the Treatment of Bronchopulmonary Dysplasia - Zhao, Shimeng; Han, Shuang (American Journal of Perinatology, 2025)
Bronchopulmonary dysplasia (BPD) is the most common chronic respiratory disease in premature infants and affects their survival rate and quality of life. There are no reliable interventions for the prevention or treatment of BPD, but the emergence of mesenchymal stem cell (MSC) therapies has brought new hope. Research has shown that paracrine may be the therapeutic mechanism of action underlying physiological improvements in the lungs of BPD patients treated with MSC therapy. The therapeutic vector in the MSC secretome comprises exosomes with low immunogenicity and stability, and that can easily cross the blood-brain barrier. In the future, exosomes may become the preferred treatment for BPD in clinical settings. Here, we review the progress of preclinical research on the use of MSC-derived exosomes as a promising treatment option for BPD.
Keywords: mesenchymal stem cell; exosomes; therapy; bronchopulmonary dysplasia